Anticonvulsant fatalities reported to the American Association of Poison Control Centers 2000 - 2019. (March 2023) - Greene, Spencer C.; Wyatt, Kimberly; Cates, Alexis L.; Weiss, Sarah
Highlights: In exposures reported to America's poison centers, carbamazepine, gabapentin, lamotrigine, phenytoin, and valproic acid are the anticonvulsants most commonly associated with fatalities. Most anticonvulsant fatalities occur in the setting of acute-on-chronic overdose. Most fatalities associated with phenytoin were attributed to therapeutic errors and adverse reactions. In exposures reported to poison centers, mortality from anticonvulsant exposures is low. Abstract: Background: Anticonvulsants are frequently prescribed, and exposures are commonly reported to American Association of Poison Control Centers sites. The purpose of this study was to describe the epidemiology of fatalities associated with oral anticonvulsant use, including patient demographics, specific medications, and the circumstances surrounding the deaths. Methods: This was a retrospective analysis of cases coded with oral anticonvulsants as a single substance and associated with a fatal outcome reported to the AAPCC National Poison Data System from 2000 to 2019. Polydrug ingestions and parenteral exposures were excluded. Patient characteristics, circumstances of the ingestion, specific medication, and chronicity of use were described. Results: We identified 126 cases that were classified as fatalities associated with single anticonvulsant use. The five most implicated anticonvulsants were carbamazepine, gabapentin, lamotrigine, phenytoin, and valproic acid. The majority (68.3%) of fatal cases were suicides. Phenytoin was implicated in eight (89%) adverse reactions and seven (70%) therapeutic errors. Valproic acid caused one (11.1%) adverse reaction and was associated with one (10%) therapeutic error. Three (75%) unintentional fatalities were caused by carbamazepine. The plurality (42.1%) of fatal ingestions occurred in acute-on-chronic use. An additional 40 (31.7%) were acute. Chronic use accounted for 15 (11.9%) of fatal exposures, including 5/10 of fatalities attributed to therapeutic error. The chronicity of medication use was unknown in 18 (14.3%) of fatal ingestions. Narrative summaries were available in 14 cases. Four of the patients presented to the emergency department with minimal symptoms. The other 10 had varying degrees of central nervous system (CNS) depression. Seizures were observed in six cases. Hyperammonemia was reported in seven of nine valproic acid ingestions. Conclusions: Fatalities associated with isolated anticonvulsant use are uncommon and typically occur following intentional overdoses. Fatal adverse reactions and therapeutic errors are most associated with phenytoin use and disproportionately affect elderly patients.